Philosophy teaching in non-formal spaces: notes of an experience - Pinto, Silmara Cristiane [UNESP]; Rosa, Sara Morais da [UNESP]; Gelamo, Rodrigo Pelloso [UNESP]; Garcia, Amanda Veloso [UNESP]; Menezes, Manoela Paiva [UNESP] (Univ Federal Santa Maria, 2015)
This article presents the findings of the university extension project Philosophy teaching in non-formal spaces and explains both the process of its implementation in practical terms and its philosophical developments. The general idea was to create a space to offer an experience at philosophizing, different from the one established in formal settings (school). Due to previous experiences regarding Philosophy teaching in institutional formalities, we tried to overflow the limits of these spaces, by converting the classical teaching into a dialogical dimension of learning and creating new spaces for thinking. In summary, this article has allowed us to explore some implications about what we have planned and henceforth what we have been experiencing: our own construction of meaning about teaching and learning Philosophy, especially of what it means to think philosophically.
Keywords: Philosophy teaching; Signs; Philosophical experience